The Roma in Romanian History - Viorel Achim (Book collections on Project MUSE., 1998)
One of the greatest challenges during the enlargement process of the European Union towards the east is how the issue of the Roma or Gypsies is tackled. This ethnic minority group represents a much higher share by numbers, too, in some regions going above 20% of the population. This enormous social and political problem cannot be solved without proper historical studies like this book, the most comprehensive history of Gypsies in Romania. It is based on academic research, synthesizing the ent ...